Non-pharamacological Interventions for Preeclampsia Management in Pregnant Women: A Literature Review - Widiasih, Restuning; Darmawan, Cahya Widyarahayu; Nugroho, Carissa Muthia Putri; Safitri, Dania Iva; Mumtazah, Dina Zahrotunnisa; Indriani, Novi; Aulia, Rahma Elfa; Solihin, Yasmin Salsabila (Universitas Padjadjaran, 2024)
Background: Preeclampsia is one of the leading causes of high maternal and child mortality worldwide, including Indonesia. Comprehensive studies on the application of non-pharmacological approach in reducing preeclampsia symptoms are still limited. This review aims to identify the effectiveness of non-pharmacological nursing interventions for preeclampsia in pregnant women. Methods: A literature search was conducted to identify relevant articles in three databases of PubMed, EBSCOHost, and Scopus. The studies reviewed were in English on the effectiveness of various non-pharmacological interventions for pregnant women with preeclampsia. The article selection was in accordance to the PRISMA guidelines for scoping reviews using the terms (“preeclampsia” OR “pre-eclampsia”) AND (“nursing intervention” OR “nursing care”) AND (“blood pressure” OR “blood pressure determination” OR “arterial pressure”). Selected studies were based on original research, either a randomized clinical tial or quasi-experimental studies, focusd on pregnant women or mothers with preeclampsia, and were published in the last ten years (2014-2024). Journal eligibility was assessed using the Joanna Briggs Institute Critical Appraisal. Results: The number of articles reviewed was seven. Findings suggest that pharmacologic management plays an important role in the control of preeclampsia, but non-pharmacologic interventions also provide significant benefits with a lower risk of adverse effects. Various non-pharmacological interventions that have been proven effective in reducing blood pressure in pregnant women with preeclampsia are Progressive Muscle Relaxation (PMR), breathing exercise, stretching exercise, autogenic training, and foot massage. Conclusion: Integration of non-pharmacological interventions in the management of preeclampsia is very important to reduce blood pressure and improve maternal and fetal well-being. Expanding the implementation of the interventions mentioned in the study should be done in further studies to measure its effects on the quality of life of the pregnant women and their compliance in preeclampsia management.Keywords: Nursing interventions, Preeclampsia, Pregnancy